2009
DOI: 10.1007/dcr.0b013e3181b550bf
|View full text |Cite
|
Sign up to set email alerts
|

Stapled Transanal Rectal Resection for Obstructed Defecation: A Cautionary Tale

Abstract: Stapled transanal rectal resection can be performed on a day-case basis with high levels of patient satisfaction. Incontinence and constipation are improved. However, significant morbidity occurs in 7% of patients, and urgency of defecation persists beyond six months in 11%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 30 publications
5
23
0
1
Order By: Relevance
“…[25][26][27] Similar studies published earlier have mentioned that defecatory urgency was the most common problem reported in the immediate and intermediate recovery periods after STARR surgery. 8,24,28 Present study results confirmed that the STARR procedure was effective in relieving symptoms of SRUS, improving quality of life and overall patient's satisfaction. Considering the operative time, duration of hospital stays, and resumption of normal activity STARR is cost effective as compared to other surgical procedures available.…”
Section: Discussionsupporting
confidence: 70%
“…[25][26][27] Similar studies published earlier have mentioned that defecatory urgency was the most common problem reported in the immediate and intermediate recovery periods after STARR surgery. 8,24,28 Present study results confirmed that the STARR procedure was effective in relieving symptoms of SRUS, improving quality of life and overall patient's satisfaction. Considering the operative time, duration of hospital stays, and resumption of normal activity STARR is cost effective as compared to other surgical procedures available.…”
Section: Discussionsupporting
confidence: 70%
“…STARR was performed at The Methodist Hospital or St. Joseph Medical Center Hospital in Houston, TX by two board-certified colon and rectal surgeons (EMH and TBP) with special STARR credentials (course undertaken in a porcine animate lab (Ethicon Endo-Surgery, Inc., Cincinnati, OH) and proctorship of the initial case). Potential complications (e.g., pelvic sepsis, pain, postoperative bleeding, tenesmus, stricture, and urinary retention) [13] were described to the patient prior to surgery and informed consent was obtained. The STARR procedure was performed as previously described under general anesthesia with the patient in lithotomy position [14].…”
Section: Methodsmentioning
confidence: 99%
“…Only original papers were considered for inclusion. As 4 papers showed a clear overlap (timeframe shift) only the most recent data were considered (19,(24)(25)(26)(27)(28)(29)(30).…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%